Dynamic changes in vasohibin and nitric oxide signaling following surgical resection of head and neck squamous cell carcinoma - Tai, Ying-Hsuan; Wu, Hsiang-Ling; Chu, You-Hsiang; Wu, Cheng-Hsien; Tai, Shyh-Kuan; Lin, Tso-Chou; Ho, Shung-Tai; Lu, Chih-Cherng (World journal of surgical oncology, 2025)
Angiogenesis is essential for tumor growth and metastasis, with various molecules, including vasohibin (VASH), nitric oxide (NO), and inducible nitric oxide synthase (iNOS), implicated in its regulation and potential prognostic value in oncology. However, their roles in modulating surgery-induced angiogenesis in head and neck squamous cell carcinoma (HNSCC) remain unclear. Therefore, the objective of the study was to assess the dynamic changes in VASH, NO, and iNOS levels in HNSCC patients undergoing surgical resection. We prospectively enrolled patients with histology-proven HNSCC who underwent surgical resection of primary tumors at the medical center between May and November 2021. Non-cancer controls were recruited to compare baseline biomarker levels with those of HNSCC patients. We measured preoperative and postoperative levels of VASH1 and VASH2 in plasma and leukocytes using enzyme-linked immunosorbent assays and Western blotting, NO using nitrate/nitrite colorimetric assays, and iNOS phosphorylation levels in leukocyte membranes using Western blotting. Patients with HNSCC (n = 15) exhibited elevated baseline levels of VASH1, NO, and leukocyte-induced iNOS phosphorylation compared to non-cancer controls (n = 15). After tumor resection, plasma VASH1 levels were significantly downregulated (2233 ± 1464 pg·mL vs. 2425 ± 1493 pg·mL , p = 0.0085), while plasma VASH2 levels remained unchanged in HNSCC patients. Similarly, VASH1 levels in leukocytes were reduced after surgery (0.85 ± 0.04 fold, p = 0.0068), while VASH2 levels did not change significantly. NO levels in plasma decreased significantly following surgery (0.29 ± 0.09 fold, p = 0.0001). Conversely, iNOS phosphorylation levels in leukocytes increased after surgery (1.52 ± 0.10 folds, p = 0.0024). The 3-year overall survival rates were 85.7% in patients with lower change folds of VASH1 in leukocytes, compared to 100.0% in those with higher change folds. This study demonstrated that dynamic changes in VASH and NO signaling following tumor resection could serve as a potential indicator of tumor angiogenesis. Our findings suggest that the overall activity of the VASH pathway in leukocytes was reduced after tumor removal, highlighting the potential of leukocyte physiology as a novel biomarker for cancer surveillance and control.